CARDIOVASCULAR HEALTH EVALUATION: FORMER FACTORS — NOVEL MODEL - A. E. Imaeva; S. A. Shalnova (Кардиоваскулярная терапия и профилактика, 2015)
Cardiovascular diseases (CVD) play leading roles among the main causes of death around the globe. In 2009 the American Heart Association developed the Model of Cardiovascular Health (CVHealth) and implemented the meaning of an "ideal", "average" and "poor" CVHealth. In assessment of CVHealth there are 7 parameters: glucose level, cholesterol level, blood pressure, smoking cessation, body mass index, physical activity and healthy food. After creation of this model, there were studies of its efficacy, and efficacy of the prevention procedures. It was revealed that the prevalence of an "ideal" CVHealth is very low, <1%, and it is necessary to pay attention to these "ideal" parameters that might be a strong predictor of morbidity as mortality from CVD. Therefore, the implementation of this score can affect positively the morbidity and mortality from CVD, by development of procedures for healthy life style in children, adolescents and youths, as for an increase of sensitivity of the people to the meanings of healthy life style.